2018
DOI: 10.1175/jas-d-17-0347.1
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Turbulence in the Boundary Layer of Hurricane Rita (2005) during an Eyewall Replacement Cycle

Abstract: The structure of coherent turbulence in an eyewall replacement cycle in Hurricane Rita (2005) is presented from novel airborne Doppler radar observations using the Imaging Wind and Rain Airborne Profiler (IWRAP). The IWRAP measurements and three-dimensional (3D) wind vector calculations at a grid spacing of 250 m in the horizontal and 30 m in the vertical reveal the ubiquitous presence of organized turbulent eddies in the lower levels of the storm. The data presented here, and the larger collection of IWRAP me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 44 publications
5
23
0
Order By: Relevance
“…The only in situ data of this kind was collected in regions either 100 km away from the hurricane eyewall or in weak tropical storms [25][26][27][28]. Note that a new airborne Doppler radar dataset from the Imaging Wind and Rain Airborne Profiler (IWRAP) is able to provide three-dimensional winds, deep into the hurricane boundary layer, at high resolution (~200 m horizontal and 30 m vertical), which will be useful for characterizing the boundary layer height using dynamical metrics [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The only in situ data of this kind was collected in regions either 100 km away from the hurricane eyewall or in weak tropical storms [25][26][27][28]. Note that a new airborne Doppler radar dataset from the Imaging Wind and Rain Airborne Profiler (IWRAP) is able to provide three-dimensional winds, deep into the hurricane boundary layer, at high resolution (~200 m horizontal and 30 m vertical), which will be useful for characterizing the boundary layer height using dynamical metrics [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Guimond et al. (2018) found that RV structure could extend up to several kilometers in radar observations. The introduction of LE effects into the PBL scheme led to better wind profile simulations that are more similar to radar observations.…”
Section: Evaluation Resultsmentioning
confidence: 99%
“…The production term is normalized by , where is the average characteristic eddy velocity of and is the characteristic eddy length scale of 2 km (Guimond et al. 2018 b ). While to the best of the authors’ knowledge no data at a similar Reynolds number are available for comparison, hopefully these scale factors will facilitate comparisons between these results and future studies.…”
Section: Sfs Energy Transfer Component Breakdownmentioning
confidence: 99%
“…Our focus in this paper is on these larger-scale turbulent structures with wavelengths of approximately 2 km that span at least the full depth of the HBL (Guimond et al. 2018 b ), which is typically approximately 1 km. To the best of the authors’ knowledge, there are no systematic studies of the full energy transfer on these scales in the HBL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation